2013
DOI: 10.1007/s10035-013-0427-7
|View full text |Cite
|
Sign up to set email alerts
|

A device for the measurement of the horizontal to vertical stress ratio in powders

Abstract: A new experimental device for the measurement of the hzorizontal to vertical stress ratio was developed. The tester is designed to conduct the requiredmeasurements using a single standard load cell without the need to apply strain gauges on custom built parts.Three different procedures were tested with free-flowing incompressible powders to determine the most precise procedure. This optimal procedure included the preliminary twisting of the cell lid to pre-shear the sample and was modified to conduct experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…As previously mentioned Salehi et al [15] reported that the critical opening size of the silo for the tested biomass materials was not adequately predicted by the Jenike procedure using data obtained with a Schulze ring shear tester. On the other hand, similar tests carried out on wood powders showed a good agreement between Jenike theory predictions and experimentally determined critical silo openings [26]. This suggests that a possible reason may consist of the limitations of the Schulze ring shear tester in measuring the flow properties of materials with large particle sizes.…”
Section: Jenike Discharge Prediction Modellingsupporting
confidence: 58%
See 1 more Smart Citation
“…As previously mentioned Salehi et al [15] reported that the critical opening size of the silo for the tested biomass materials was not adequately predicted by the Jenike procedure using data obtained with a Schulze ring shear tester. On the other hand, similar tests carried out on wood powders showed a good agreement between Jenike theory predictions and experimentally determined critical silo openings [26]. This suggests that a possible reason may consist of the limitations of the Schulze ring shear tester in measuring the flow properties of materials with large particle sizes.…”
Section: Jenike Discharge Prediction Modellingsupporting
confidence: 58%
“…This method is a function of material bulk flow properties, hopper geometry and wall friction, and hopper inclination angle. According to Barletta and Poletto [13], the Jenike method's critical silo opening size to avoid arching for wedge shape silo estimation and the experimental results are in good agreement for wood powders. However, the Jenike method has been shown to be inadequate for designing silos for biomass materials with large/ irregularly shaped particles [14,15].…”
Section: Introductionmentioning
confidence: 82%
“…There is still need for developing new device for the measurements of parameters of powdered materials. One of such device is that proposed by Barletta and Poletto (2013) who invented two half-cells with fixed one and mobile one using a single standard load cell without the need to apply strain gauges on custom built parts, as in apparatus presented in this article. Values of the parameter obtained under the loading regime were approximately 30 times lower than those for unloading.…”
Section: Resultsmentioning
confidence: 99%